Repetition in Surah Ar-Rahman: Its purposes, and the purposes of those who challenge it (Journal of Human Sciences, 2025)
This research deals with an analytical study in the field of interpretation of the Holy Qur’an, through which the verses that deal with the phenomenon of repetition in general are traced, and the connotations of this word and its fruits are revealed.  The verses are carefully studied, and the sayings of scholars and commentators in particular are studied, by studying the phenomenon of repetition.   Which involves rhetorical meanings, which are highlighting the Quranic miracle and its superior eloquence, explaining its purposes and the goals of those who challenge these methods, and responding to the suspicions they raise. chosen as a model for this study. Because it contains the largest number of verses in this field, the discussion will be limited to the concept of repetition, clarifying its meanings and interpretations, citing some of the sayings of scholars in this regard, clarifying the purposes of repetition, and addressing the issue.  Among those who challenge the phenomenon of repetition and respond to it, and then present the verses of repetition in Surat Al-Rahman, and in a position.   And based on the inferences based on the words of the commentators about these verses, and as a result, a title was given to this research, which is: Repetition in Surat Al-Rahman: its purposes, and the purposes of those who object to it.  After this arrangement comes the conclusion, which includes the most important results and recommendations.